Teachers’ and Pupils’ Attitudes and Practices towards the Use of Mother Tongue in EFL Teaching - Chikh, Mohammed Kamel; Negadi, Mohamed Nassim (جامعة أحمد دراية أدرار, 2023)
Learning is claimed to be better with fruitful results when conducted within the learners’ variety. However, when it comes to teaching EFL, most teachers tend to use only that language in the classroom. But, in reality, they face problems related to communicating with their learners. This research paper aims at investigating EFL teachers’ attitudes and practices towards the use of L1 in EFL teaching in an Algerian context at middle schools. The sample of the study consists of 70 participants; including 40 pupils and 30 English teachers from different middle schools in Tlemcen. The data collected were both qualitatively and quantitatively analysed. The results obtained reveal that both teachers and learners have positive attitudes towards using L1 in the English class, because it is considered as an auxiliary tool for them. The results also show that a wise use of L1 in the class facilitates EFL learning, and helps both teachers and learners to cope with difficult or new tasks, to motivate learners and to facilitate teacher-learner communication.
Keywords: اللغة الإنجليزية -- اللغة الأم -- العملية التعليمية -- الجزائر